2016
DOI: 10.1186/s40691-016-0074-9
|View full text |Cite
|
Sign up to set email alerts
|

Black walnut, Osage orange and eastern redcedar sawmill waste as natural dyes: effect of aluminum mordant on color parameters

Abstract: The triple bottom line can be impacted in both positive and negative ways by the use of tree sawmill waste as a natural dye. Trees contain a biomordant in the form of tannin which may eliminate the need for metallic mordants, thus reducing water, thermal energy, residual waste, and exposure to a mordant chemical. Dyeing with mill waste provides an economic option for an existing timber manufacturing byproduct. This research analyzed the impact of potassium aluminum sulfate (PAS) on dye concentration, hue, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 19 publications
1
15
0
Order By: Relevance
“…Therefore, it was observed that tannin mordanting improved color fastness to light rather than color change of the wool fabrics dyed with spent coffee extract. This result was supported by the previous reports that "tannin mordants and dyes may darken dyed textiles as they age, instead of the color fading due to exposure to washing and light (Cardon 2007;Richards and Tyrl 2005)" (Doty et al 2016). Figure 3 shows the results obtained by infrared spectroscopy analyses of the wool fabrics dyed with spent coffee extract.…”
Section: Color Revelation Characteristics Of Wool Fabrics Dyed With Ssupporting
confidence: 83%
“…Therefore, it was observed that tannin mordanting improved color fastness to light rather than color change of the wool fabrics dyed with spent coffee extract. This result was supported by the previous reports that "tannin mordants and dyes may darken dyed textiles as they age, instead of the color fading due to exposure to washing and light (Cardon 2007;Richards and Tyrl 2005)" (Doty et al 2016). Figure 3 shows the results obtained by infrared spectroscopy analyses of the wool fabrics dyed with spent coffee extract.…”
Section: Color Revelation Characteristics Of Wool Fabrics Dyed With Ssupporting
confidence: 83%
“…This on one hand leads to wastage of resources, and on the other hand their disposal poses a serious threat to the environment. Effective utilisation of this agro-waste utilisation would not only address disposal issues, but also provide additional income to the farmers or processing industries that generate the waste [29].…”
Section: Waste From Agriculturementioning
confidence: 99%
“…Eucalyptus liquid waste from lumber steaming has been used by to dye cotton [51]. Sawmill waste from Kansas black walnut, osage orange, and eastern red cedar timber have been used as dyestuffs for textiles [29]. Waste bark extracts from Turkish red pine (Pinus brutia Ten) have been applied on cotton, flax, wool, tencel, polyamide and acrylic [46].…”
Section: Waste From Forestrymentioning
confidence: 99%
“…However, environmentalists and scientists point out that synthetic dyes pollute water and soil (Brigden et al, 2012;Gregory, 2007). Environmental concerns have led to a growing demand for ecologically friendly textile processes and have increased interest in natural dyes because they are a biodegradable source of color (Bechtold & Mussak, 2009;Doty et al, 2016;Laughlin, 2017;Schneider-Levy, 2018). Those interested in natural dyes can learn from others on social media platforms such as Instagram, where individuals and communities provide a space to connect and share knowledge (Gauntlett, 2018).…”
Section: Natural Dyesmentioning
confidence: 99%